810Geographical disparities in diagnosis of myeloproliferative neoplasms in Australia. (2nd September 2021) - Cameron, Jessica; Fritschi, Lin; Ross, David; Anderson, Lesley Ann; Cramb, Susanna; Aitken, Joanne; Mengersen, Dist Kerrie; Duncan, Earl; Baade, Peter
Abstract: Background: Myeloproliferative neoplasms (MPNs) are a relatively new group of blood cancers arising from genetic mutations in haematopoietic stem cells. Diagnostic delay is associated with thromboses, strokes and heart attacks. We investigated geographic variation in diagnosis and survival for classic MPNs. Methods: Data for classic MPNs were obtained from the Australian Cancer Database. Leroux spatial models for incidence and survival were fitted using CARBayes, WinBUGS via R and tests for spatial clustering were conducted. Results: The age-standardised incidence rate was 4.9 (95% CI: 4.8-5.0) per 100, 000 person-years during 2007-2016 with relative survival of 78% (77%, 79%) at 5 years after diagnosis. Strong evidence of spatial variation in incidence was observed (p < 0.001), with incidence rates low in Tasmania (4.2 per 100, 000 person-years, 95% CI: 3.5-5.0) and Western Australia (6.1, 5.6-6.6) and high in Victoria (9.5, 9.2-9.9) and Queensland (10.6, 10.2-11.1). Differences between states and territories could not be explained by population rates of genetic testing or the proportion of registered cases with histological evidence. Conclusions: Stark spatial differences in incidence rates of classic MPNs suggest that varying diagnosis and registration patterns between states results in under-recognition, and potentially undertreatment. It is imperative that reporting is consistent so that sound evidence is available for efforts to reduce disparities in diagnosis and management. Key messages: Early identification of MPNs is crucial, however, strong spatial geographical variation in incidence rates suggest diagnostic and notification practices may not be consistent across the country.